До історії вивчення скіфських пам’яток Надпоріжжя (безкурганний могильник біля Третього кар’єру Дніпробуду) - Могилов, О.Д. (Археологія і давня історія України, 2022)
У статті висвітлено матеріали безкурганного
некрополя біля Третього кар’єру Дніпробуду, який
вивчався в ході масштабних археологічних робіт
при побудові Дніпрогесу в 1931 р. During the period between First and Second World
Wars a large-scale archaeological research was carried
out in connection with the construction of the Dnieper
Hydroelectric Station (the DniproHES). Large number
of ancient sites felt into the area of flooding and destruction.
In order to study them the Dniprobud expedition
was organized which carried out significant
excavations in 1927—1932 under the head of D. I. Yavornytskyi.
Among the excavated sites there was also the necropolis
located on the eastern side of the 3rd quarry of
the Dniprobud, on the right bank of the modern Zaporizhzhya
city, on a high rocky slope of the Old Dnieper.
The works took place in September — early October
1931 headed by the Dniprobud expedition member
P. I. Smolichev. At the time of the excavation most of
the necropolis included more than a dozen stone pavements
had been destroyed. Only two burials survived
under single-layer stone pavements with a diameter
of 5.6—8 m. A menhir-like stone was recorded near
grave 1. Single burials of the necropolis were made in
catacombs with stone chambers’ barriers. Supposedly
a child and a warrior were buried. Child’s burial was
without grave goods. The man was accompanied by the
arrowheads and pot.
The necropolis near the 3rd quarry of Dniprobud is a
part of the whole system of Scythian necropolises with
moundless burials on the Lower Dnieper. The area
of such necropolises coincides with the Scythian settlement
network. Settlements are often located near
such necropolises which gives grounds to connect these
burials with the population of such settlements. The
topography of the necropolis on the slope above the
Dnieper is typical for burial mounds in the Dnieper
area. Burials made of stone are also typical for this region.
This tradition dates back to the Bronze Age and is
also known during the pre-Scythian period. The graves
near the 3rd quarry of Dniprobud can be dated to the
4th century BC based on the types of burial structures
and grave goods. Moreover, they can be considered to
belong to the local ordinary nomadic Scythian population
which began to change their way of life to the settled
one. However, it preserved typical traditions of nomads’
funeral rites. In addition, the implementation of
burials under stone pavements may indicate that the
new ethnic substrate of the region, formed in Scythian
Age, may have included some part of the aboriginal
population that lived here since the Bronze Age and
pre-Scythian times.